Opportunities of Electron Microscopy When Solving Cryobiological Tasks. Retrospective Analysis - Repin , Nikolay; Marchenko, Larisa; Govorukha, Tatyana; Goltsev, Anatoliy (Problems of Cryobiology and Cryomedicine, 2022)
The history of the development and use of low-temperature electron microscopic methods of freeze-fracture, freeze-substitution and others in cryobiological research at the Institute for Problems of Cryobiology and Cryomedicine of the National Academy of Sciences of Ukraine is presented in this article. These methods’ possibilities in studying the processes of crystal formation in cryoprotectant solutions, cell suspensions, and tissues under various freezing conditions are demonstrated. Some results of the analysis of ultrastructural changes in biological systems of various organization levels, at different stages of ontogenesis, under the influence of cooling in a wide temperature range (from 37 to –196°C) are presented. The use of a high resolution electron microscopic method in combination with an accessory technical equipment and some methodological techniques allowed to obtain fundamental results important for cryobiology on ice crystals formation and localization in the intracellular volume, the temperature-dependent transmembrane proteins redistribution, changes in the ultrastructure of erythrocytes and their membranes during hypothermic storage. Probl Cryobiol Cryomed 2022; 32(1): 003–013